"An Unqualified Human Good"? On Rule of Law, Globalization, and Imperialism. Issue 4 (19th May 2017) - Brown, Mark
Abstract : Forty years ago, E. P. Thompson praised the English rule of law forged during the bloody and fractious eighteenth century, calling it not only "an unqualified human good, " but also a "cultural achievement of universal significance." This article examines colonial rule‐of‐law development as another example of law and state building. Both have relevance for contemporary rule‐of‐law programming in the Global South where Thompson's "cultural achievement" has resisted fabrication by legal technicians. The problems faced today are not new, for colonial rulers also engaged with complex indigenous norms and forms and sought to balance universal principles with political control imperatives. Contra arguments about colonial "lawfare, " colonial rule of law often frustrated authoritarian tendencies while developing new forms of legal subjectivity and avenues for redress of grievances. Using data from the Indian province of Punjab, the article illustrates how historical case studies might aid contemporary rule‐of‐law programming in the Global South.